Multi-wavelength coupling effect of laser-induced defect damage in beam splitter films captured by a three-dimensional spatially and temporally resolved method. (October 2020) - Shan, Chong; Zhao, Xiaohui; Gao, Yanqi; Zhao, Yuanan; Rao, Daxing; Cui, Yong; Li, Cheng; Hu, Guohang; Ma, Weixin; Sui, Zhan; Shao, Jianda
Highlights: Three-dimensional spatially and temporally resolved method for accurate defect damage thresholds of optical films. Defects on substrate are significant sources of splitter film damages. Defect damage threshold of 532 nm laser decreases continuously with 1064 nm laser fluence increases. Abstract: In this paper, we propose a three-dimensional spatially and temporally resolved method for measuring laser-induced damage fluence by identifying the time onset of defect damage and the damage location in the three-dimensional coordinate system of a Gaussian beam. When considering a second-harmonic beam splitter as an example, the defect fluence of fundamental wave (1064 nm) and second harmonic wave (532 nm) simultaneous irradiation is captured accurately by the proposed method. The defect damage threshold of a second-harmonic beam splitter and the coupling effect between multi-wavelength lasers during defect damage initiation are investigated. Our test method can not only identify complex multi-wavelength laser coupling damage mechanisms that traditional test methods cannot observe, but also provides a new method for obtaining accurate defect information for optical films, which is helpful for improving the laser resistance ability of optical films.